Procopius De aedificiis 4.2.1–22 on the Thermopylae Frontier - Cherf, William Joseph (Byzantinische Zeitschrift, 2011)
This article compares topographical and archaeological remains of the Thermopylae frontier with the ancient testimonia of the sixth century historian Procopius of Caesareia ( De aedificiis 4.2.1.–22). It was revealed that: many of the frontier fortifications described were initially built before the sixth century; the fortified κλεισούρα mentioned should be equated with the Dhéma Pass; and the commercial settlement of Myropóles is best identified with the modern village of Káto Dhió Vouná. Written in Attic prose, this passage represents a rhetorical exercise, the climax of which turned not on the ancient battlefield of Thermopylae, but rather on a mountain pass and it's highway that neutralized the Thermopylae defenses if they were ever controlled by the enemy. We were told that only the Emperor Justinian's wisdom could grasp this critical fact. Additionally, Procopius employed many rhetorical devices in this narrative: τóπος, χρóνος, , ἄγαλμα, ἔκφρασις, πανηγρικóς and employed imperial propaganda, praise, and exaggeration as well. In short, the passage is a classic example of selective story telling that may have found its inspiration in the Hunnic raid of 539/540 and the Herodotean account of the Persian invasion of 480 BC. While Procopius' account remains our best topographical description of the late antique Thermopylae frontier, one can only say that more archaeological questions were left unanswered than were resolved. In short, as an archaeological source, the De aedificiis is a disappointing and vexing resource filled with equivocations. Finally, one may doubt that Procopius ever did visit the Thermopylae frontier, even though during his career he certainly had ample opportunity to do so. His account, therefore, must have been based upon secondary sources, whether imperial archival material, itineraries, or military staff reports and were not the result of personal autopsy.